Ionizing Particle Radiation as a Modulator of Endogenous Bone Marrow Cell Reprogramming: Implications for Hematological Cancers - Muralidharan, Sujatha; Sasi, Sharath P.; Zuriaga, Maria A.; Hirschi, Karen K.; Porada, Christopher D.; Coleman, Matthew A.; Walsh, Kenneth X.; Yan, Xinhua; Goukassian, David A. (Frontiers in Oncology, 2015)
Exposure of individuals to ionizing radiation (IR), as in the case of astronauts exploring space or radiotherapy cancer patients, increases their risk of developing secondary cancers and other health-related problems. Bone marrow (BM), the site in the body where hematopoietic stem cell (HSC) self-renewal and differentiation to mature blood cells occurs, is extremely sensitive to low dose IR, including irradiation by high-charge and high-energy particles (HZE). Low dose IR induces DNA damage and persistent oxidative stress in the BM hematopoietic cells. Inefficient DNA repair processes in HSC and early hematopoietic progenitors can lead to an accumulation of mutations whereas long-lasting oxidative stress can impair hematopoiesis itself, thereby causing long term damage to hematopoietic cells in the BM niche. We report here that low dose 1H- and 56Fe-IR significantly decreased the hematopoietic early and late multipotent progenitor (E- and L-MPP, respectively) cell numbers in mouse BM over a period of up to 10 months after exposure. Both 1H- and 56Fe-IR increased the expression of pluripotent stem cell markers Sox2, Nanog and Oct-4 in Late-MPPs 2 and 10 months post-IR exposure. We postulate that low doses of 1H- and 56Fe-IR may induce endogenous cellular reprogramming of BM hematopoietic progenitor cells to assume a more primitive pluripotent phenotype; IR-induced oxidative DNA damage may lead to mutations in these BM progenitors. This could then be propagated to successive cell lineages. Persistent impairment of BM progenitor cell populations can disrupt hematopoietic homeostasis and lead to hematologic disorders and these findings warrant further mechanistic studies into the effects of low dose IR on the functional capacity of BM-derived hematopoietic cells including their self-renewal and pluripotency.